Delayed Titanium Hypersensitivity and Retained Foreign Body Causing Late Abdominal Complications - Jain, Molly S. (Case Rep Surg, 2021)
Titanium is a known metal used widely in the medical field and can cause allergic reactions with complications. Our case is about a 28-year-old female presenting with a spectrum of abdominal symptoms with a complicated medical history. The abdominal pain is associated with titanium allergy reaction from previously inserted titanium-based surgical clips. This patient is concurrently found to have a retained pigtail catheter in the cecum discovered incidentally through radiology. We discuss the presentation, investigations, and treatment of this unusual case. The case also unfolds rare differential diagnoses to keep in mind when encountering a patient with abdominal pain and associated nonspecific symptoms.